A Study on Kentoshi Abeno Nakamaro’s Prolonged Stay in Tang China and the Psychological Analysis of His Longing for Homeland - Zhaohui Bu (Forest Chemicals Review, 1970)
Abeno Nakamaro, a student of Kentoshi (Japanese missions to Tang China), was a special figure of ancient Sino-Japanese exchange. More than 1300 years ago, he arrived in China during the Tang Dynasty as a student sent by Japanese government to study various Chinese cultures and served as a permanent official in China. The study of his life in Tang dynasty China for over fifty years has not been systematic or well documented. This study investigates both the political and private aspects of his stay in China over a period of fifty years in the Tang Dynasty through research and analysis of Chinese and Japanese historical sources and poetic writings, and summaries the reasons for his stay in China as a voluntary stay in the early stages of his life due to his personal “ attachment to Chinese culture”, a retaining by the Tang government for his official duties in the middle stages, and a lifelong stay in the later stages of his life hindered by the harsh natural environment in which he had set out on his return journey. The study also focuses on Abe's longing for his homeland in a foreign country, China, from the perspective of the psychological correlation between changes occurring in the human psyche and changes in the social environment, and takes the Chinese poems and waka composed by Abeno Nakamaro as the main clues to analyze his homesickness in various periods in China, and concludes that Abe's longing for his homeland did not disappear or diminish as his surroundings in China became better, but grew stronger over time. This leads to the point that the psychological emotion of homesickness is a specific human psychology, a psychological emotion that arises as a result of changes in the social environment, yet resists changes in the social environment. This is evident in the case of Abe and other members of Kentoshi. This study enriches the knowledge of this particular figure of Abeno Nakamaro, and also provides a scholarly reference for the study of members of Japanese missions to Tang China as well as their psychological emotions.